2021
DOI: 10.3390/ijms22157771
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Temperature-Dependent Kinetics of Oculocutaneous Albinism-Causing Mutants of Tyrosinase

Abstract: Human tyrosinase (Tyr) is a glycoenzyme that catalyzes the first and rate-limiting step in melanin production, and its gene (TYR) is mutated in many cases of oculocutaneous albinism type phenotype in patients with OCA1 have only began to be examined and remain to be delineated. Here, we analyze the temperature-dependent kinetics of wild-type Tyr (WT) and two OCA1B mutant variants (R422Q and P406L) using Michaelis–Menten and Van’t Hoff analyses. Recombinant truncated human Tyr proteins (residues 19–469) were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Tyrosinase (TYR) is the key rate-limiting enzyme in the process of melanogenesis, and TYR activity strongly affects the entire pigmentation process [ 27 ]. The higher activity of TYR could lead to a higher amount of melanogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Tyrosinase (TYR) is the key rate-limiting enzyme in the process of melanogenesis, and TYR activity strongly affects the entire pigmentation process [ 27 ]. The higher activity of TYR could lead to a higher amount of melanogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the squalene epoxidase catalyzing the first oxygenation step in the triterpenoid and phytosterol biosynthetic pathway is one of the key enzymes in this pathway ( Gao et al, 2016 ). Tyrosinase catalyzed both the first and key step in melanin production ( Wachamo et al, 2021 ). PGM catalyzed the branch point reaction-the interconversion of glucose-1-phosphate from glucose-6-phosphate in carbohydrate metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…In P406L, the OCA1B-related mutation in tyrosinase significantly impacts small-molecule substrate binding. We previously showed that the association of L-DOPA with R422Q and P406L mutant variants followed by dopachrome formation is a complex reaction supported by enthalpic and entropic forces [ 17 , 18 ]. rTyr has a higher turnover number as compared with both R422Q and P406L.…”
Section: Discussionmentioning
confidence: 99%
“…Although we saw a change in rTyr activity in R422Q and P406L mutant variants, we found similar Km values and thermodynamic behavior for other proteins. This led us to deduce that the change in activity might be due to the allosteric effect [ 18 , 29 ]. Utilizing molecular docking and MD simulations, we demonstrated that, in a water environment, only DHI docked with proper orientation to P406L’s active site and then remained stable after MD simulations ( Figure S3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation